PEMBATAS KECEPATAN MAKSIMUM PADA KENDARAAN MENGGUNAKAN RPM MOTOR DC DENGAN SISTEM PERINGATAN SMS - Syarif Hidayat; M Iqbal Harish (Sekolah Tinggi Teknik - PLN, 2016)
In the process of creating an innovation to the growing number of vehicles as well as considering the risks that happens then raised an idea to reduce the number of accidents. A maximum speed limiting devices on vehicles with warning system via SMS (Short Message Service) seeks to reduce the occurrence of traffic accidents, and improving comfort and safety in driving for yourself or other motorists. The tool is powered by mikrontroller Atmega 8 as a control system with photodiode sensor and infrared as detection speed.